S13-1: The Development of a Global Physical Literacy (GloPL) Action Framework: Process and Outcome (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical literacy (PL) emphasises the integration of physical, affective, cognitive, and social elements to promote health-enhancing physical activity. Although the concept has gained significant attention in research, practice, and policy over the last two decades, the field is characterised by segmented actor networks, narrow country foci, and a lack of prospective orientation. Therefore, the goal of this study was to: (a) define goals, principles, actions, and pathways that advance the PL field, and (b) subsequently derive a ‘Global Physical Literacy (GloPL) Action Framework’.Methods: Leveraging the benefits of collective intelligence, we conducted a group Delphi study with individuals representing: geographical regions (59 individuals on behalf of 46 countries), themes of special interest (seven themes/individuals), and 19 academic societies/organisations, including the HEPA Europe network. The representatives independently generated ideas through online surveys (Qualtrics) with the potential to significantly advance the PL field. The ideas were subjected to four-eye reflexive thematic analysis (NVivo v14.23.3), informing the subsequent discussions in three online meetings split into two hemispheres. All decisions were supported by formal voting with pre-defined agreement thresholds for the first (≥67%) and second (≥50%) voting rounds.Results: The reflexive thematic analysis resulted in 857 codes hierarchically bundled to five meta-themes: advocacy, practice, education, assessment, research. The members discussed 15 central topics, of which six reached agreement in the first and nine in the second voting round. Combined, the most important recommendations include (sorted by discussion time): instead of forcing a global PL definition, the field requires an obligatory core set of elements/principles, allowing for national or regional specificities (89.7%); physical education curricula worldwide should align with the principles of PL (93.9%); PL should be highlighted on the global sport agenda (92.0%); and the field of PL can benefit from strengthening links to the sustainable development goals (66.0%).Conclusion: The results of the 15 topics inform the content of the first ‘Global Physical Literacy (GloPL) Action Framework’. Its release will guide actions in the fields of ‘advocacy’, ‘practice’, ‘education’, ‘assessment’, and ‘research’.Funding/Support Source: This study is supported by the first author’s postdoctoral research fellowship.Keywords: Health promotion, holistic, lifespan, physical activity